PROBLEMATIKA PENGAWASAN BANK PERKREDITAN RAKYAT SYARIAH DI PAMEKASAN - Zainal Abidin (Jurnal Sosial Humaniora, 2025)
DPS It is urgent to give serious respond on the existing opinion that syariah banking is practically similar to conventional one. In fact, they are different in certain folds. One of the distinctive points is that the former has been equipped by a supervision board---Dewan Pengurus Syariah (DPS). This article exposes two things: firstly, it discusses how DPS operates its supervision function against BPR Syariah SPM in Pamekasan; secondly, it describes how DPS contributes its supervision function toward BPR Syariah SPM Pamekasan as an effort to keep the BPR Syariah be in the syariah (Islamic law) track. This research employs case study design of qualitative approach. This study results the followings---firstly, DPS has systematically supervised the BPRS SPM. The supervision is regularly undergone at least once a month toward the administration (contract transaction) and customer. Secondly, DPS BPRS SPM runs important contribution to enhance the syariah values of BPRS SPM. DPS both supervise and advise BPRS SPM to uphold the syariah principles in running the whole banking operations.